The Emerging Role of Proline in the Establishment and Functioning of Legume-Rhizobium Symbiosis - Sabbioni, Giuseppe; Forlani, Giuseppe (Frontiers in Plant Science, 2022)
High levels of some enzymes involved in proline synthesis and utilization were early found in soybean nodules, and rhizobial knockout mutants were shown to be defective in inducing nodulation and/or fixing nitrogen, leading to postulate that this amino acid may represent a main substrate for energy transfer from the plant to the symbiont. However, inconsistent results were reported in other species, and several studies suggested that proline metabolism may play an essential role in the legume-Rhizobium symbiosis only under stress. Different mechanisms have been hypothesized to explain the beneficial effects of proline on nodule formation and bacteroid differentiation, yet none of them has been conclusively proven. Here we summarize these findings, with special emphasis on the occurrence of a legume-specific isoform of 1-pyrroline-5-carboxylate synthetase, the enzyme that catalyses the rate-limiting step in proline synthesis. Data are discussed in view of recent results connecting the regulation of both, the onset of nodulation and proline metabolism, to the redox status of the cell. Full comprehension of these aspects could open new perspectives to improve the adaptation of legumes to environmental stress.